Early Results of Ablation in Left Approach Atrioventricular Nodal Reentry Tachycardia (AVNRT) - Yavuzkir, Mustafa; Cakmak, Tolga; Korkmaz, Hasan; Harman, Murat; Akbulut, Mehmet (Elsevier Science Inc, 2013)
[Abstract Not Available]
29th Turkish Cardiology Congress of the Turkish-Society-of-Cardiology (TSC) with International Participation -- OCT 26-29, 2013 -- Antalya, TURKEY